Valuing Landscape in Classical Antiquity : Natural Environment and Cultural Imagination - McInerney, Jeremy (Mnemosyne, Supplements Ser, 2016)
‎Contents -- ‎List of Illustrations -- ‎List of Contributors -- ‎Chapter 1. General Introduction (SluiterSluiter) -- ‎Part 1. Mountains -- ‎Chapter 2. Mount Etna in the Greco-Roman imaginaire: Culture and Liquid Fire (Buxton) -- ‎Chapter 3. Strabo's Mountains (König) -- ‎Chapter 4. Mountain, Myth, and Territory: Teuthrania as Focal Point in the Landscape of Pergamon (Williamson) -- ‎Part 2. Underground and Underworld -- ‎Chapter 5. Diving Underground: Giving Meaning to Subterranean Rivers (Baleriaux) -- ‎Chapter 6. Experience and Stimmung: Landscapes of the Underworld in Seneca's Plays (Winter) -- ‎Part 3. The Sacred -- ‎Chapter 7. Birds around the Temple: Constructing a Sacred Environment (Miles) -- ‎Chapter 8. Juno Sospita and the draco: Myth, Image, and Ritual in the Landscape of the Alban Hills (Hermans) -- ‎Chapter 9. Charismatic Landscapes? Scenes from Central Greece under Roman Rule (Robinson) -- ‎Part 4. Battlefields and Memory of War -- ‎Chapter 10. Heritage in the Landscape: The 'Heroic Tumuli' in the Troad Region (Minchin) -- ‎Chapter 11. Land at Peace and Sea at War: Landscape and the Memory of Actium in Greek Epigrams and Propertius' Elegies (Reitz-Joosse) -- ‎Chapter 12. Thessaly as an Intertextual Landscape of Civil War in Latin Poetry (Ambühl) -- ‎Part 5. Moving Around -- ‎Chapter 13. Migration and Landscapes of Value in Attica (Kellogg) -- ‎Chapter 14. Songs of Homecoming: Sites of Victories and Celebrations in Pindar's Victory Odes (Ćulumović) -- ‎Chapter 15. The Mythical Landscapers of Augustan Rome (Crofton-Sleigh) -- ‎Chapter 16. Polyvalent Tomi: Ovid's Landscape of Relegation and the Romanization of the Black Sea Region (Pieper) -- ‎Chapter 17. Stones, Names, Stories, and Bodies: Pausanias before the Walls of Seven-Gated Thebes (Hawes) -- ‎Index of Greek Terms -- ‎Index of Latin Terms -- ‎Index Locorum -- ‎General Index.